(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
Using Nehari manifold method combined with fibring maps, we show the existence of nontrivial, weak, positive solutions of the nonlinear ψ-Riemann-Liouville fractional boundary value problem involving the p-Laplacian operator, given by where λ>0, 0